2006
DOI: 10.1148/radiol.2393050458
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Stenosis: Comparative Evaluation of 16–Detector Row CT and Echocardiography

Abstract: Planimetric measurements of AVA with retrospectively electrocardiographically gated 16-detector row CT allow classification of AS that is similar to that achieved with measurements by using echocardiographic methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(42 citation statements)
references
References 31 publications
2
35
0
5
Order By: Relevance
“…CT may be performed and is useful to confirm AS severity and to define valve anatomy [25][26][27]. This study provides data of coronary ostia locations and aortic root dimensions in patients with severe tricuspid AS and demonstrates differences in these patients when compared with the controls.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…CT may be performed and is useful to confirm AS severity and to define valve anatomy [25][26][27]. This study provides data of coronary ostia locations and aortic root dimensions in patients with severe tricuspid AS and demonstrates differences in these patients when compared with the controls.…”
Section: Discussionmentioning
confidence: 82%
“…This selection bias, however, is generated by the fact that AS generally occurs in the elderly population. Third, results from TTE in the assessment of AS were not compared with results from CT, but has been amply documented in the literature [25,26,35,36]. Finally, the impact of the preprocedural anatomical assessment on patient outcome was not assessed in the present study.…”
Section: Limitationsmentioning
confidence: 97%
“…For diagnosis of AI, TTE, TEE, angiography or MRI can be applied. Non-invasive assessment for both AS and AI is also possible with CT [16,17].…”
Section: Patient Selectionmentioning
confidence: 99%
“…During the remaining part of the cardiac cycle, the tube output was reduced. When employed for coronary CT angiography, this technique has been shown to achieve an overall ionizing radiation exposure savings of 30-50% (10,11) have shown that MDCT can be used for anatomic delineation of the aortic valve area by performing MPR of axial images using a 16-channel ECGgated CTA during coronary imaging. We used 75% of the R-R interval to generate MPR using 64-channel MDCT during CTA of the aorta.…”
Section: Image Acquisitionmentioning
confidence: 99%